2006
DOI: 10.1093/nar/gkj474
|View full text |Cite
|
Sign up to set email alerts
|

HEN1 recognizes 21-24 nt small RNA duplexes and deposits a methyl group onto the 2' OH of the 3' terminal nucleotide

Abstract: microRNAs (miRNAs) and small interfering RNAs (siRNAs) in plants bear a methyl group on the ribose of the 3′ terminal nucleotide. We showed previously that the methylation of miRNAs and siRNAs requires the protein HEN1 in vivo and that purified HEN1 protein methylates miRNA/miRNA* duplexes in vitro. In this study, we show that HEN1 methylates both miRNA/miRNA* and siRNA/siRNA* duplexes in vitro with a preference for 21–24 nt RNA duplexes with 2 nt overhangs. We also demonstrate that HEN1 deposits the methyl gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
278
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(296 citation statements)
references
References 23 publications
12
278
0
6
Order By: Relevance
“…We and others have shown that all types of siRNAs (except nat-siRNAs that have not been tested) are methylated in vivo in a HEN1-dependent manner (Akbergenov et al, 2006;Ebhardt et al, 2005;Li et al, 2005). Our biochemical studies with recombinant HEN1 protein also demonstrated that HEN1 is a siRNA methyltransferase (Yang et al, 2006).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…We and others have shown that all types of siRNAs (except nat-siRNAs that have not been tested) are methylated in vivo in a HEN1-dependent manner (Akbergenov et al, 2006;Ebhardt et al, 2005;Li et al, 2005). Our biochemical studies with recombinant HEN1 protein also demonstrated that HEN1 is a siRNA methyltransferase (Yang et al, 2006).…”
Section: Introductionsupporting
confidence: 65%
“…Using purified recombinant GST-HEN1 protein, we demonstrated that HEN1 is a miRNA methyltransferase that acts on miRNA/miRNA★ in a sequence-independent manner . HEN1 can methylate small RNA duplexes ranging from 19 to 26 nt in size but has the best efficiency on 21 to 24 nt small RNA duplexes (Yang et al, 2006). In addition, it has a strict requirement for the 2 nt 3′ overhang and for the presence of both the 2′ and 3′ OH on the ribose of the 3′ terminal nucleotide, characteristic features of Dicer products (Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These phenotypes were later revealed to be attributable to widespread reductions in sRNAs and their activities. In subsequent work by the Chen laboratory, the HEN1 protein was shown to function as a methyltransferase; the methyltransferase activity is specific to sRNAs, adding a 2 0 -O-methyl group on the 3 0 -terminal nucleotide of template sRNAs Yang et al 2006). In more recent work, the crystal structure of HEN1 suggests that it can specifically recognize the sRNA duplex as its template via multiple RNA-binding domains and a methyltransferase domain (Huang et al 2009).…”
Section: Discovery Of Hen1 and Its Conserved Function In Many Speciesmentioning
confidence: 99%
“…The Chen laboratory and collaborators have published biochemical data demonstrating the specificity of HEN1 activity. Their initial work in this area showed the methyltransferase activity by which HEN1 transfers a methyl group to the 2 0 hydroxyl of the 3 0 -terminal nucleotide of a sRNA Yang et al 2006). They showed that both strands of either an miRNA/miRNA Ã duplex siRNA/siRNA Ã duplex are methylated in vitro, and HEN1 has a preference for 21-24-nucleotide RNA duplexes with a 2-nucleotide overhang typical of DICER cleavage (Yang et al 2006).…”
Section: Discovery Of Hen1 and Its Conserved Function In Many Speciesmentioning
confidence: 99%
See 1 more Smart Citation